Presupposition Analysis in The Help Film (2011) - Puspita Dewi, Hergianti; Setyowati, Ririn; Alim Akbar Nasir, Muhammad (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
ABSTRACT This research examines the use of presupposition in the dialogue and script of the film The Help (2011) through George Yule's presupposition theory. Presuppositions are background assumptions held by the speaker and play a role in communication to convey information indirectly. George Yule identifies six types of presuppositions: existential, factive, lexical, structural, non-factive, and counterfactual. The Help film is set in 1960s Mississippi during the Civil Rights Movement and explores the complex relationship between black maids and their white employers. This research focuses on the dialogues and scripts of three film characters, Aibileen Clark, Minny Jackson, and Eugenia Phelan (Skeeter), to investigate how types of presuppositions are represented in the dialogues and scripts. This research shows how presuppositions contribute to understanding implicit information using a pragmatic approach. Socio-cultural contexts are used to understand the way presuppositions interpret utterances. In this study, all six types of presuppositions: existential, factive, lexical, structural, non-factive, and counterfactual were found in the film's dialogue. Structural presuppositions were the most common type, and non-factive presuppositions were the least found by the researcher. This study shows that presuppositions are essential to convey messages implicitly, enhancing the researcher's understanding of character interactions through the context of the unfolding situation and the characterization of Aibileen as the main character. Keywords: context, film, presupposition, The Help film